Exerkines and long-term synaptic potentiation: Mechanisms of exercise-induced neuroplasticity - Vints, Wouter A.J.; Levin, Oron; Fujiyama, Hakuei; Verbunt, Jeanine; Masiulis, Nerijus (Frontiers in neuroendocrinology, 2022)
[Display omitted] •Cognitive deficits are associated with impairments in long-term potentiation (LTP).•Acute and chronic, cardiovascular and resistance exercise facilitate LTP processes.•Exerkines may underlie the mechanism of the exercise-induced facilitation of LTP.•Exercise and subject characteristics influence exerkine levels following exercise. Physical exercise may improve cognitive function by modulating molecular and cellular mechanisms within the brain. We propose that the facilitation of long-term synaptic potentiation (LTP)-related pathways, by products induced by physical exercise (i.e., exerkines), is a crucial aspect of the exercise-effect on the brain. This review summarizes synaptic pathways that are activated by exerkines and may potentiate LTP. For a total of 16 exerkines, we indicated how blood and brain exerkine levels are altered depending on the type of physical exercise (i.e., cardiovascular or resistance exercise) and how they respond to a single bout (i.e., acute exercise) or multiple bouts of physical exercise (i.e., chronic exercise). This information may be used for designing individualized physical exercise programs. Finally, this review may serve to direct future research towards fundamental gaps in our current knowledge regarding the biophysical interactions between muscle activity and the brain at both cellular and system levels.